2021
DOI: 10.1590/fst.16320
|View full text |Cite
|
Sign up to set email alerts
|

The use of white striped chicken breasts on the quality of nuggets and hamburgers

Abstract: The objective of this study was to evaluate physically and chemically chicken breasts with different degrees of white striping (WS), as well as its effect on the process and quality of nuggets and hamburgers. Chicken breasts fillets were obtained from male chicken broilers weighing approximately 3 kg at the slaughterhouse and classified based on the WS degree as normal, moderate or severe. Chemical composition was evaluated (moisture, crude protein, fat, mineral matter and total collagen), as well as pH, color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Initial pH analysis of the samples showed no significant differences for the groups tested, with no effect on EC. Bordignon et al (2021), evaluated the quality of nuggets with WS chicken breasts. These studies revealed no significant difference regarding emulsion stability.…”
Section: Samplesmentioning
confidence: 99%
“…Initial pH analysis of the samples showed no significant differences for the groups tested, with no effect on EC. Bordignon et al (2021), evaluated the quality of nuggets with WS chicken breasts. These studies revealed no significant difference regarding emulsion stability.…”
Section: Samplesmentioning
confidence: 99%